ICT web - analysis of the Brazilian governmental web - Ganzeli, Heitor de Souza; Bressan, Graça; Moreiras, Antônio Marcos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
The World Wide Web is the most popular application throughout the Internet and, since its creation, it has changed people's lives in lots of ways, hence, it has become subject to several social, technological, economical and political researches. This paper presents both a project called ICT Web (Measuring Information and Communication Technologies for Development – Web) and the results it has obtained by studying the Brazilian Governmental Web. Some of the discussed topics are as follows: the importance of Open Standards, and how their conformity evaluation can be used to measure and classify the quality of Web sites. Also, more technical issues related to web crawler and web analysis tools are shown in order to reveal how all data were retrieved. Not only does this work point out some characteristics of the Brazilian governmental Web sites, which helps the creation of policies that improve this Web sites quality, but also it establishes a series of features to compare the perceived quality between Web domains.